PEMANFAATAN VEGETASI MANGROVE DI PULAU PADANG TIKAR KECAMATAN BATU AMPAR KABUPATEN KUBU RAYA - . Ratnasari; M Dirhamsyah (Universitas Tanjungpura, 2017)
Utilization of natural resources by the community sometimes does not pay attention to the limits of ability or environmental carrying capacity in the regeneration process for sustainable life cycle, both biologically, physically, ecologically and economically. Optimal and environmentally sound utilization and management of natural resources is required to support the sustainability of natural resources including mangrove forests. Mangrove forest is one type of tropical rainforest located along the coastline of tropical waters. This forest is a transition of terrestrial and marine environment habitat. One of the mangrove forest in West Kalimantan is located on Pulau Padang Tikar Batu Ampar Sub-district of Kubu Raya Regency with mangrove forest area of approximately 58,953 Ha which consists of 11 villages inside the forest. The purpose of this research is to know the types of mangrove vegetation and the utilization of mangrove vegetation by the community in 11 villages of Pulau Padang Tikar. This research uses survey method with interview technique. Numbers of respondents were 10 people from each village (total number 110 respondents) in Pulau Padang Tikar. Results of the research found 20 mangrove vegetation species found in the community and 9 types of mangrove vegetation are used for firewood, building material, charcoal, honey bee cultivation and herbal medicines. The species found were Acanthus ilicifolius, Acrostichum aureum, Avicennia sp. Amyema anisomeres, Bruguiera parviflora, Excoecaria agallocha, Heritiera globosa, Kandelia candel, Lumnitzera littorea, Nypa fruticans, Rhizophora sp., Sonneratia alba, Sonneratia caseolaris, Xylocarpus granatum, Oncosperma tigilarium, Hibiscus tiliaceus, Ipomea pescaprae, Sonneratia sp, Bruguiera cylindrica and Sonneratia ovata back.Keywords: Batu Ampar, Kubu Raya Regency, mangrove, Pulau Padang Tikar, Utilization